Diacron reactive oxygen metabolites and biological antioxidant potential tests for patients with age-related macular degeneration - Matsuura, Toshiyuki (BMC Ophthalmol, 2020)
BACKGROUND: Previously, we showed that serum malondialdehyde (MDA) was significantly higher in patients with neovascular age-related macular degeneration (nAMD) than in those without AMD. The Diacron reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) tests are known markers of oxidative stress. The aim of this study was to use d-ROMs and BAP tests to evaluate changes in systemic oxidative stress in patients with nAMD. METHODS: Blood serum samples were collected from 34 patients with nAMD (mean age: 76.5 ± 7.7 years; 22 men) and 20 control subjects (mean age: 62.9 ± 14.0 years; 10 men), and d-ROMs and BAP tests were examined. RESULTS: In men, the mean level of d-ROMs for the nAMD patients was significantly higher than that for the controls (312.0 ± 52.4 vs. 275.1 ± 45.5 U.CARR, respectively; P < .05). There was a significant correlation between d-ROM level and CNV lesion area in the male nAMD group (r = .42, P = .05). There were no significant differences in mean BAP test results between the nAMD patients and controls for either sex (men: 2241 ± 549 vs. 2136 ± 246 μmol/L; women: 2263 ± 292 vs. 2335 ± 161 μmol/L). CONCLUSION: The d-ROMs test may provide a useful indicator of nAMD in men but not in women.